Extraordinarily persistent photo-induced carriers mediated by interfacial exciton splitter in organic single-crystalline semiconductors - Nobutaka Osakabe; Akifumi Yamamura; Tatsuyuki Makita; Yasunari Tamai; Shun Watanabe; Jun Takeya (Applied Physics Express)
Exciton dissociation into free electron-hole carriers is a central issue in optoelectronic devices. Despite recent progress in free-carrier generation due to an admixture of organic compounds, strategies to prolong the lifetime of photo-induced carriers are limited. Herein, we present a proof-of-concept of efficient exciton dissociation via heterogeneous device engineering; an insulating polymer layer adjacent to organic semiconductors (OSCs) in conjunction with an application of electrical voltage can capture photogenerated electrons selectively, and the resulting semipermanent built-in electric field gives rise to extraordinarily persistent photo-induced carriers, which lasts for more than half a year in single-crystalline OSCs.